Linking Hydrothermal Activity With Organic Matter Accumulation in the Chang 7 Black Shale of Yanchang Formation, Ordos Basin, China - Yuan, Wei; Liu, Guangdi; Zhou, Xiaoxing; Bulseco, Ashley (Frontiers in Earth Science, 2022)
The Chang 7 black shale in the Upper Triassic Yanchang Formation is the principal source rock of Mesozoic oil-bearing system in the southwest Ordos Basin, containing high abundances of organic matter and hydrocarbon potential. Our study discusses the role of lake-bottom hydrothermal activities in the enrichment of organic matter during the deposition of the Chang 7 black shale. A large number of basement faults developed in the interior and margin of the Ordos Basin, which provided channels for the upwelling of deep hydrothermal fluids. Moreover, the strong tectonic activities during the Chang 7 sedimentary period provided dynamic conditions for the activation of the faults and the upwelling of hydrothermal fluids. The occurrence of hydrothermal activities in the Chang 7 sedimentary period is proved by the evidences of mineralogy petrology, stable isotopes, major, and trace elements in the black shale. Abundant nutrients that were transported from the lake-bottom hydrothermal fluids into lake water promoted the lacustrine surface primary productivity, and then increased the supply of sedimentary organic matter. At the same time, the degradation of a large number of organic matters increased consumption of oxygen in the water column, resulting in the formation of bottom-water anoxic environments. The accumulation of organic matter in sediments was controlled by the lake-bottom hydrothermal activities by the means of increasing the lacustrine surface paleoproductivity and promoting the formation of anoxic environments.